PENGEMBANGAN BAHAN AJAR MICROTEACHING UNTUK MELATIHKAN KOMPETENSI PEDAGOGIK YANG MENGINTEGRASIKAN TIK DAN NILAI-NILAI KARAKTER - Sanusi, Sanusi; Murtafiah, Wasilatul; Krisdiana, Ika (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2016)
Position of teachers as professionals in the Act No. 14 of 2005, serves to increase the dignity of teachers as well as its role as a learning agent to improve the quality of national education. Teachers as professionals implies that teachers work can only be done by someone who, among others, have certain competencies, namely: pedagogical competence, personal competence, social competence, and professional competence. The purpose of this research is to developteaching materials for train pedagogical Microteaching integrating communications and information technology the values of character. Urgency of research is the importance ofcommunication and information technology mastery character values by students through lectures integrated Microteaching. This research is the development that follows the mechanism and design of the development of teaching materials (Fenrich, 1997). The steps include the development of teaching materials analysis phase (analysis), planning (planning), design (design), development (development), implementation (implementation), evaluation and revision (evaluation and revision). The initial phase of the study in the first year is to develop an instrument for the investigation, analysis (analysis), planning (planning) and designing (design) prototype. In the first year of teaching materials that have been designed include: SAP, Textbook, Media, and theAssessment Guidelines. In the second year was followed by the development (development) Microteaching teaching materials and implements (implementation) in the lecture. The results showed that the Microteaching Subjects that have been developed to train integrating ICT pedagogical competence and character values can be regarded as a good learning tool because it meets the criteria of validity, practicality, and effectiveness. Integrating ICT pedagogicalcompetence and character values can be trained.Position of teachers as professionals in the Act No. 14 of 2005, serves to increase the dignityof teachers as well as its role as a learning agent to improve the quality of national education.Teachers as professionals implies that teachers work can only be done by someone who, amongothers, have certain competencies, namely: pedagogical competence, personal competence,social competence, and professional competence. The purpose of this research is to developteaching materials for train pedagogical Microteaching integrating communications andinformation technology the values of character. Urgency of research is the importance ofcommunication and information technology mastery character values by students through lecturesintegrated Microteaching. This research is the development that follows the mechanism and designof the development of teaching materials (Fenrich, 1997). The steps include the development ofteaching materials analysis phase (analysis), planning (planning), design (design), development(development), implementation (implementation), evaluation and revision (evaluation andrevision). The initial phase of the study in the first year is to develop an instrument for theinvestigation, analysis (analysis), planning (planning) and designing (design) prototype. In thefirst year of teaching materials that have been designed include: SAP, Textbook, Media, and theAssessment Guidelines. In the second year was followed by the development (development)Microteaching teaching materials and implements (implementation) in the lecture. The resultsshowed that the Microteaching Subjects that have been developed to train integrating ICTpedagogical competence and character values can be regarded as a good learning tool because itmeets the criteria of validity, practicality, and effectiveness. Integrating ICT pedagogicalcompetence and character values can be trained.